A study of the direct costs of anesthesiology and reanimatology in Clinical center Serbia - Majstorović Branislava A.M; Milaković Branko D.; Naumović Tamara S.; Bukumirić Zoran M.; Marković Srđan Z.; Kastratović Dragana A.; Vukašinović Ivan D.; Lađević Nebojša G. (Srpsko lekarsko drustvo, 2018)
Introduction: Modern health care implies the continuous development of human resources and the application of pharmacoeconomic analyzes during the introduction of new methods of treatment in medicine. Aim: The aim of the paper is to compare and analyze: 1) the number of: operated patients, provided anesthesia services, hospital days in ICU and surgery interventions; 2) distribution of anesthetic services: general anesthesia, local anesthesia and anesthesia procedures and 3) the values of direct costs of anesthesiology and reanimatology, in 2006 and 2015 in order to propose measures of rationalization and savings of funds. Methods: This paper is part of an academic IV phase study, conducted at the Clinical Center of Serbia (CCS) with the permission of the Ethical Committee of the Medical Faculty of the University of Belgrade (470 / IV7) and harmonized with the European Union Directive. Direct costs of anesthesiological services of the Center for Anesthesiology and Reanimatology, by department of anesthesia in the maternal surgical clinics of the Clinical Center of Serbia in Belgrade, during 2006 and 2015, are included and analyzed. The subjects were all anesthetized patients, both sexes, children and adults. The numeric data is processed by Microsoft Office Excel 2003 and SPSS for Windows. For the analysis of the statistical significance of the number of patients, anesthesiologic services, hospital days in Intensive Care Units and surgical procedures was used Wilcox test. In order to analyze the percentage distribution of funds in the category of direct costs (personal costs, drugs, materials, analyzes and medical equipment), in 2015 compared to 2006 was used the hi-square matching test. Results: There is a statistically significant difference in the frequency of service categories within the scope of services in 2015 compared to 2006 (p <0.001), indicators of hospital work. There is a statistically significant difference in the frequency of anesthetic services in 2015 compared to 2006 (p <0.001). There is a statistically significant difference in the total direct cost of anesthesiology and reanimatology between 2006 and 2015 (p = 0.043). There is a statistically significant difference in the frequency of direct cost categories in 2015 relative to 2006 (p <0.001). In the period of recession and transition in 2006, 42% of funds for personal expenses were separated, for medicines and materials 29%, analyzes and medical devices 29%. The direct costs of anesthetic services would be at the annual level of 10% relative to the means of surgical activity. Without taking into account methodological concerns (organizational changes, introduction of new groups of drugs in the responsibility of anesthesiologists, limiting legal regulations, higher prices), after a ten-year period, the ratio of direct costs was changed in 2015, so that personal costs amount to 4%, drugs and materials amount to 94% and analysis and medical equipment amount to 2%. Conclusion: 1. The 10-fold decrease in personnel costs in 2015 statistics is certainly not a consequence of a change in the methodology, but a constant, chronic and progressive impairment of vocational work in total health care costs. 2. Anesthetist services are only visible during their stay in the operating room. It is evident that most of the services performed in: preoperative assessment and preparation, immediate postoperative and delayed, chronic treatment of critical patients, are either unrecognized or incorrectly attributed to surgical specialties. 3. The quality of the statistical data presented is indicating the lack of interest of the hospital administration in analyzing and utilizing the collected data in reducing and rationalizing health care costs. 4. Academic multicenter studies in pharmacoeconomics are needed to help doctors to achieve a better uniform standards of providing anesthesia services using evidence based medicine.